2020
DOI: 10.4209/aaqr.2019.03.0106
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Fine Particulate Matter on Visibility at Incheon International Airport, South Korea

Abstract: Low visibility at an airport causes significant flight delays, thereby reducing the airport's capacity. To better understand its contributing factors, the present study examined the visibility at Incheon International Airport, South Korea, and its relationship with meteorological conditions as well as particulate matter (PM; viz., PM 2.5 and PM 10 ) concentrations for the period of 2015-2017. A censored regression model was developed to quantitatively describe the changes in visibility, and the results demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 33 publications
1
19
0
Order By: Relevance
“…The increase of values of Rh, P, and PM 10 results in the decrease of Vis, while the increase of T results in an increase of Vis. These results are in the agreement with earlier studies (e.g., Deng et al, 2014;Majewski et al, 2015;Aman et al, 2019;Araghi et al, 2019;Won et al, 2020). The concentrations of CO and SO 2 are independent variables only in the model where Vis lim1 = 10 km, and the increase of both of them decreases visibility.…”
Section: The Logistic Regression Modelsupporting
confidence: 93%
“…The increase of values of Rh, P, and PM 10 results in the decrease of Vis, while the increase of T results in an increase of Vis. These results are in the agreement with earlier studies (e.g., Deng et al, 2014;Majewski et al, 2015;Aman et al, 2019;Araghi et al, 2019;Won et al, 2020). The concentrations of CO and SO 2 are independent variables only in the model where Vis lim1 = 10 km, and the increase of both of them decreases visibility.…”
Section: The Logistic Regression Modelsupporting
confidence: 93%
“…The PM 2.5 affects visibility significantly more than the CPM, but in weather conditions such as dust and haze as well as low RH, the CPM effects are sometimes not negligible. Increasing wind speed is associated with decreasing PM 2.5 concentration and visibility recovery, whereas the CPM exhibits a relationship in which its concentration increases with wind speed 46 . This is also related to the generation and transport mechanisms of the PM 10 , as revealed by previous studies 45 , 60 .…”
Section: Discussionmentioning
confidence: 94%
“…This is explained by the negative correlations in the RH–WS plot (− 0.27), demonstrating that low wind speed and high humidity values are related to high PM 2.5 concentrations. Since these conditions are common under stable atmospheric conditions, several studies have revealed their association with PM 2.5 stagnation 18 , 45 , 46 . In the WX–CPM box plot, the CPM commonly displays high concentrations in dust, while in the WX–PM 2.5 box plot, the highest PM 2.5 concentrations occur in haze and dust.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Various adverse effects of heavy metals on human, animal, plant, soil and aquatic health also abound ( Ogunkunle et al., 2013 ; Ogunkunle and Fatoba, 2014 ). By absorption and scattering of radiations, particles have been known to affect visibility with attendant effects of flight navigation ( Won et al., 2020 ).…”
Section: Common Anthropogenic Air Pollutants: Sources and Adverse Effmentioning
confidence: 99%